2010
DOI: 10.1159/000279887
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Body Count and Stable Microbubble Test on Gastric Aspirates from Preterm Infants for the Diagnosis of Respiratory Distress Syndrome

Abstract: Background: Lamellar body count (LBC) in amniotic fluid is being used to identify infants at risk of respiratory distress syndrome (RDS) who would benefit from surfactant prophylaxis or very early therapy. The test in gastric aspirates of newborns has not been properly explored. Objective: The main objective of this research was to evaluate the performance of LBC alone or in combination with the stable microbubble test (SMT), done on gastric aspirates from preterm babies to predict RDS. Methods: A total of 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
0
25
1
Order By: Relevance
“…Daniel et al [23] who also used LBC in GAS for diagnosing RDS found a cut-off value of 42,000/µl. Our lower cut-off value is partly due to centrifugation of the GAS, which can reduce LBC [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daniel et al [23] who also used LBC in GAS for diagnosing RDS found a cut-off value of 42,000/µl. Our lower cut-off value is partly due to centrifugation of the GAS, which can reduce LBC [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our lower cut-off value is partly due to centrifugation of the GAS, which can reduce LBC [15]. Furthermore, we diagnose infants with moderate to severe RDS with need for surfactant supplementation, while Daniel et al [23] diagnosed all infants with RDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specific tests for surfactant deficiency such as measurement of surfactant proteins, lecithin/sphingomyelin ratios and phosphatidylcholine/sphingomyelin ratios require laboratories, are expensive and time-consuming and have not been applied to infants treated with CPAP. More recently, lamellar body count in gastric aspirate, a more objective test, has been found to be comparable to SMT in predicting RDS but requires a laboratory with a centrifuge and cell counter [16]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2006, a small study showed the utility of the test to predict the need for surfactant in nonventilated preterm infants [4]. In a recent study, the test showed good sensitivity (94%) and specificity (86%) for the diagnosis of respiratory distress syndrome when performed in gastric fluid [5]. We have introduced the SMT as part of routine care of all very-low-birth-weight infants at our service, to assist in the decision to give early surfactant in symptomatic infants on CPAP.…”
mentioning
confidence: 99%